Using motivational interviewing to promote adherence to antiretroviral medications: A randomized controlled study - DiIorio, C. (2008)
The primary aim of this study was to test an intervention to support antiretroviral medication adherence among primarily low-income men and women with HIV. The study was a randomized controlled trial (Get Busy Living) with participants assigned to treatment (Motivational Interviewing [MI]) and control groups. Participants were recruited from an HIV/AIDS clinic in Atlanta, Georgia, US. Of those referred to the study, 247 completed a baseline assessment and were enrolled with 125 randomized to the intervention group and 122 to the control group. Participants were patients beginning antiretroviral therapy or changing to a new drug regimen. The intervention consisted of five MI sessions delivered by registered nurses in individual counselling sessions. Participants were paid for each session attended. The intervention sought to build confidence, reduce ambivalence and increase motivation for ART medication-taking. Medication adherence was measured by the Medication Event Monitoring System (MEMS(®)) from the time of screening until the final follow-up conducted approximately 12 months following the baseline assessment. Participants in the intervention condition showed a trend towards having a higher mean percent of prescribed doses taken and a greater percent of doses taken on schedule when compared to the control group during the months following the intervention period. This effect was noted beginning at about the eighth month of the study period and was maintained until the final study month. Although the finding was weaker for overall percent of prescribed doses taken, the results for the percent of doses taken on schedule suggests that the MI intervention may be a useful approach for addressing specific aspects of medication adherence, such as adherrence to a specified dosing schedule.